Janus structure photo-thermal evaporation film for seawater desalination and preparation method of Janus structure photo-thermal evaporation film
By using the double-layer thin film design of the Janus structure photothermal evaporation membrane, the problems of salt precipitation blockage and photothermal imbalance in high-salinity seawater environments are solved, achieving efficient water evaporation under low light intensity and wide-angle conditions, which is suitable for large-scale seawater desalination.
Patent Information
- Application Number
- CN202511595552.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2025-12-16
AI Technical Summary
Existing photothermal evaporation membranes are prone to salt precipitation and blockage in high-salinity seawater environments, resulting in an imbalance between photothermal conversion and water supply. Furthermore, they suffer from insufficient light capture efficiency under low-intensity wide-angle incident conditions, making it difficult for devices to achieve long-term, efficient, and stable freshwater production.
A Janus-structured photothermal evaporation film is constructed using non-solvent-induced phase separation and nanosecond laser etching techniques to create a bilayer film. The upper layer is a superhydrophobic photothermal functional layer, and the lower layer is a hydrophilic water transport layer. The photothermal synergy of heteronaphthalene biphenyl polyarylether sulfone ketone and nano molybdenum disulfide forms a micro-nano structure to achieve full-spectrum solar light absorption and rapid water evaporation.
It achieves excellent water evaporation performance under low light intensity and wide-angle sunlight conditions, has self-driven salt repulsion capability, is suitable for large-scale construction, and has a simple and convenient process.
Smart Images

Figure CN121130673A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of water treatment and functional materials, and relates to a Janus structure photothermal evaporation membrane for seawater desalination and a preparation method thereof. BACKGROUND
[0002] Shortage of fresh water resources is a severe challenge to global sustainable development, which poses a general threat to human society, economic activities and ecological systems. Seawater desalination, as an important way to obtain fresh water, its technical energy consumption and cost directly determine the feasibility of application. Traditional seawater desalination technologies, such as reverse osmosis membrane method and multi-stage flash evaporation method, have been widely used, but they have the problems of high equipment investment, huge energy consumption (reverse osmosis method energy consumption is about 3-5 kWh / m 3 ) and environmental problems caused by concentrated salt water discharge. The interfacial solar steam generation technology can utilize sustainable solar energy, and only evaporate water at the gas-liquid interface, avoiding the huge heat loss caused by heating the whole water body, and is considered as a promising low-energy-consumption, distributed seawater desalination scheme.
[0003] However, the current widely studied interface photothermal evaporator, especially the single-layer homogeneous structure of photothermal material, still faces severe challenges in practical application: (1) Salt crystallization blockage: In the process of continuous evaporation, salt in water will continuously precipitate and accumulate at the evaporation interface, seriously blocking the water transport channel and light absorption channel, resulting in a sharp decline in evaporation efficiency and even functional failure; (2) Imbalance between photothermal and transport: A single hydrophilic photothermal layer easily conducts the generated heat to the lower water body, causing significant heat loss; while a single hydrophobic design is not conducive to the continuous supply of water, making it difficult to maintain a stable evaporation rate; (3) Light utilization angle sensitive: The surface microstructure optimized for vertical incident light (such as a single recess) will cause the light trapping ability to decrease significantly due to the geometric shadow effect under low solar elevation angle (such as early morning, dusk, high latitude) conditions, limiting the all-weather operation performance. Even if the photothermal material itself has a high absorption rate (≥90%), the above structural and management problems also make it difficult for the device to achieve long-term, efficient, and stable fresh water output in real high-salinity seawater environment. Therefore, the current reported studies, such as "Mussel-inspired MXene-functionalized sponge for solar-driven water purification: Photothermal-driven crude oil absorption, solar steam generation, and photothermal sterilization" (Chemical Engineering Journal, 2025, 514, 163237) and "Hierarchically Structured Black Gold Film with Ultrahigh Porosity for Solar Steam Generation" (Chemical Engineering Journal, 2022, 34, 2200108), etc. The structure still has deficiencies in coordinating efficient photothermal conversion, rapid directional water transport, wide-angle light trapping, and effective salt rejection self-cleaning in the face of complex real environment. SUMMARY
[0004] The purpose of the present application is to overcome the above-mentioned defects of the existing photothermal evaporation film in the face of high-salinity seawater, such as easy salt precipitation blockage, imbalance between photothermal conversion and water supply, and insufficient light trapping efficiency under low light intensity and wide-angle incidence conditions, and to provide a Janus structure photothermal evaporation film with self-driven salt rejection and high-efficiency interface evaporation capacity and a preparation method thereof.
[0005] The technical solution of the present application:
[0006] A Janus structured photothermal evaporation membrane for seawater desalination is a double-layer composite structure with asymmetric wettability, which is obtained by compounding an upper superhydrophobic photothermal functional layer and a lower hydrophilic water transport layer.
[0007] The upper film composite solution for forming the superhydrophobic photothermal functional layer comprises heteronaphthalene biphenyl polyarylether sulfone ketone, polydimethylsiloxane, nano-molybdenum disulfide and N-methyl pyrrolidone, and the mass percentage of each component is as follows:
[0008] Heteronaphthalene biphenyl polyarylether sulfone ketone: polydimethylsiloxane: nano-molybdenum disulfide: N-methyl pyrrolidone = 1:0.2:0.01:5.
[0009] The lower film composite solution for forming the hydrophilic water transport layer comprises quaternary aminated heteronaphthalene biphenyl polyarylether sulfone ketone and N-methyl pyrrolidone, and the mass percentage of each component is as follows:
[0010] Quaternary aminated heteronaphthalene biphenyl polyarylether sulfone ketone: N-methyl pyrrolidone = 1:3-10.
[0011] A preparation method of a Janus structured photothermal evaporation membrane for seawater desalination, the steps are as follows:
[0012] Step 1, dissolve heteronaphthalene biphenyl polyarylether sulfone ketone in N-methyl pyrrolidone, then add polydimethylsiloxane, stir and mix, then add nano-molybdenum disulfide dispersion, stir and mix to obtain an upper film composite solution;
[0013] Step 2, after the upper film composite solution in step 1 is formed by a blade coating method, immerse it in deionized water for 48h for non-solvent induced phase separation, and then dry to obtain a superhydrophobic photothermal functional layer surface of the upper layer;
[0014] Step 3, design a micro-nano structure on the upper surface of the superhydrophobic photothermal functional layer surface of the upper layer in step 2 by nanosecond laser etching technology to obtain a superhydrophobic film with photothermal water evaporation performance; the parameters of the micro-nano structure design are as follows:
[0015] Laser frequency: 30KHz; current: 1A; scanning speed: 1000mm / s; laser scanning interval: 0.02mm; scanning track: cylindrical;
[0016] Step 4, dissolve quaternary aminated heteronaphthalene biphenyl polyarylether sulfone ketone in N-methyl pyrrolidone to obtain a lower film composite solution;
[0017] Step 5, uniformly coat the lower film composite solution in step 4 on the lower surface of the superhydrophobic photothermal functional layer surface in step 2 by a blade coating method, then immerse it in ethyl acetate for 24h for non-solvent induced phase separation, and then dry to obtain a double-layer composite film.
[0018] Step 6, the lower surface of the double-layer composite film in step 5 is designed with micro-nano structure by nanosecond laser etching technology to obtain a hydrophilic surface with a rapid water passage; the parameters of the micro-nano structure design are as follows:
[0019] Laser frequency: 30KHz; current: 1A; scanning speed: 1000mm / s; laser scanning interval: 0.02mm; scanning track: net format.
[0020] Innovations of the present application: the present application uses a method combining non-solvent induced phase separation and laser etching to construct a Janus structured photo-thermal water evaporation double-layer film with heteronaphthalene biphenyl polyarylether sulfone ketone as a base material. The heteronaphthalene biphenyl polyarylether sulfone ketone in the lower film is modified by quaternary amination and has excellent hydrophilicity, and a stable super-hydrophobic upper surface is constructed on the heteronaphthalene biphenyl polyarylether sulfone ketone / polydimethylsiloxane film, combined with non-solvent induced phase separation to construct a rapid Janus water transport channel. In addition, the photo-thermal synergistic effect between the heteronaphthalene biphenyl polyarylether sulfone ketone material and nano-molybdenum disulfide can realize solar light absorption of full spectrum (250-2500nm). Combined with the micro-nano structure formed on the surface after laser etching, the present application can realize excellent water evaporation performance under the conditions of low light intensity (0.1 sun) and solar incident angle of 0-60°.
[0021] Advantages of the present application:
[0022] (1) The present application uses heteronaphthalene biphenyl polyarylether sulfone ketone as a stable film matrix, uses non-solvent induced phase separation method and nanosecond laser etching technology to construct Janus structure on the upper surface and the lower surface of the double-layer film, so that the upper layer of the composite film has photo-thermal super-hydrophobicity, the lower layer has hydrophilicity, and an excellent rapid water transport channel is formed, and at the same time, excellent water evaporation function can be realized under the conditions of low light intensity and wide-angle solar irradiation;
[0023] (2) The present application has wide-angle photo-thermal water evaporation capacity on the basis of existing super-hydrophobic film, uses the photo-thermal synergistic effect of heteronaphthalene biphenyl polyarylether sulfone ketone and nano-molybdenum disulfide to absorb full spectrum solar light, and combines laser etching to have excellent absorption capacity, so that solar energy can be converted into heat energy to raise the surface temperature and realize long-term effective water evaporation. Most importantly, the present application has low environmental dependence due to the special Janus structure design, and still has good water evaporation effect under the conditions of low light intensity and large-angle oblique light source, and has good potential application value;
[0024] (3) The double-layer Janus structure photo-thermal water evaporation film prepared by the present application has simple process and convenient operation, and is suitable for large-area large-scale construction. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 Micro-morphology diagram of the upper surface of the double-layer film of Example 1.
[0026] Figure 2 Micro-morphology diagram of the lower surface of the double-layer film of Example 1.
[0027] Figure 3 Micro-morphology diagram of the cross section of the double-layer film of Example 1. DETAILED DESCRIPTION
[0028] The specific embodiments of the present application are further illustrated in conjunction with the accompanying drawings and technical solutions.
[0029] Example 1
[0030] The present embodiment provides a Janus film with photothermal water evaporation performance, which is obtained by film forming treatment of a composite film solution:
[0031] The upper layer composite film solution comprises heteronaphthalene polyphenyl ether sulfone ketone, polydimethylsiloxane, nano-molybdenum disulfide and N-methyl pyrrolidone, and the mass percentage of each component is as follows:
[0032] Heteronaphthalene polyphenyl ether sulfone ketone: polydimethylsiloxane: nano-molybdenum disulfide: N-methyl pyrrolidone = 1:0.2:0.01:5.
[0033] The preparation method of the above-mentioned upper film comprises the following steps:
[0034] (1) 1 g of heteronaphthalene polyphenyl ether sulfone ketone is dissolved in 5 mL of N-methyl pyrrolidone, and stirred at room temperature until completely dissolved to obtain a heteronaphthalene polyphenyl ether sulfone ketone solution, then 0.2 g of polydimethylsiloxane is added to the heteronaphthalene polyphenyl ether sulfone ketone solution, and after stirring at room temperature for 1 h, 0.01 g of nano-molybdenum disulfide-containing dispersion liquid obtained by ultrasonic treatment is added, and continuously stirred at room temperature for 1 h to obtain a composite film solution.
[0035] (2) The composite film solution in step (1) is prepared into a composite film by non-solvent induced phase separation method: the composite solution is coated by using a 400 μm doctor blade, then soaked in deionized water for 48 h, during which the water is changed twice, and dried at 60 o C for 12 h to evaporate the solvent, forming a film with a thickness of about 200 μm.
[0036] (3) The composite film in step (2) is designed with micro-nano structure on the upper surface by nanosecond laser etching technology, and the laser frequency is set to 30 KHz; current: 1 A; scanning speed: 1000 mm / s; laser scanning interval: 0.02 mm; and the laser scanning pattern track is cylindrical.
[0037] (4) 1 g of the quaternary aminated heteronaphthalene-biphenyl poly(arylene ether sulfone ketone) was dissolved in 5 mL of N-methyl pyrrolidone, and stirred at room temperature until completely dissolved to obtain a quaternary aminated heteronaphthalene-biphenyl poly(arylene ether sulfone ketone) solution.
[0038] (5) The composite film solution in step (4) was uniformly coated on the lower surface of the composite film obtained in step (3) by a blade coating method, and then a double-layer film was prepared by a non-solvent induced phase separation method: the composite solution was coated by a 400 μm blade, and then soaked in ethyl acetate for 48 h, during which the ethyl acetate was replaced twice, and dried at 60 o C for 12 h to evaporate the solvent, thereby forming a double-layer film.
[0039] (6) The lower surface of the double-layer film in step (5) was designed with a micro-nano structure by a nanosecond laser etching technology, with a laser frequency of 30 KHz; current: 1 A; scanning speed: 1000 mm / s; laser scanning interval: 0.02 mm; and the laser scanning pattern track was a mesh format.
[0040] The upper surface of the photo-thermal water evaporation double-layer film prepared in this example exhibited a uniform protruding micro-nano structure, the lower surface exhibited a uniform porous structure, and the cross-section exhibited a uniform through-hole structure, as shown in FIGS. Figure 1 、 2 and 3.
[0041] Example 2
[0042] Example 2 is a double-layer film with photo-thermal water evaporation performance, which was prepared by basically the same preparation process as Example 1, except that the laser scanning pattern track in step (3) was changed to a mesh format.
[0043] The upper and lower surfaces of the photo-thermal water evaporation double-layer film prepared in this example both exhibited a uniform porous structure, and the cross-section exhibited a uniform through-hole structure.
[0044] Example 3
[0045] Example 3 is a double-layer film with photo-thermal water evaporation performance, which was prepared by basically the same preparation process as Example 1, except that step (1) was modified as follows: 1 g of the heteronaphthalene-biphenyl poly(arylene ether sulfone ketone) was dissolved in 5 mL of N-methyl pyrrolidone, and stirred at room temperature until completely dissolved to obtain a heteronaphthalene-biphenyl poly(arylene ether sulfone ketone) solution, 0.01 g of nano-molybdenum disulfide was added to the dispersion liquid obtained by ultrasonic treatment, and continuously stirred at room temperature for 1 h to obtain a composite film solution.
[0046] Comparative Example 1
[0047] Comparative Example 1 is a double-layer film with photothermal water evaporation performance, which is prepared by using the same preparation process as Example 1, the difference is that only steps (1), (2), (3), (4) and step (5) are performed, and step (6) is not performed.
[0048] Comparative Example 2
[0049] Comparative Example 2 is a double-layer film with photothermal water evaporation performance, which is prepared by using the same preparation process as Example 1, the difference is that only steps (1), (2), (4), (5) and step (6) are performed, and step (3) is not performed.
[0050] Comparative Example 3
[0051] Comparative Example 3 is a double-layer film with photothermal water evaporation performance, which is prepared by using the same preparation process as Example 1, the difference is that only steps (1), (2), (4) and step (5) are performed, and steps (3) and step (6) are not performed.
[0052] Comparative Example 4
[0053] Comparative Example 4 is a single-layer film with photothermal water evaporation performance, which is prepared by using the same preparation process as Example 1, the difference is that only steps (1), (2), (3) and step (4) are performed, and steps (5) and step (6) are not performed.
[0054] Comparative Example 5
[0055] Comparative Example 5 is a single-layer film with photothermal water evaporation performance, which is prepared by using the same preparation process as Example 1, the difference is that only steps (4), (5) and step (6) are performed, and steps (1), (2) and step (3) are not performed.
[0056] Reference Figure 1 The upper surface, lower surface and cross-sectional morphology of the Janus film prepared in Example 1 are shown, it is found that the upper surface after nanosecond laser etching forms a protrusion array and a recessed porous interlaced micro-nano structure, which has excellent light absorption effect when facing a wide-angle sunlight of 0-60°, and has excellent superhydrophobicity, with a water contact angle of 156.4°. The lower surface after laser etching enhances the hydrophilicity of the lower layer film, realizing a rapid water transport channel, when 0.8 sunlight is vertically incident, the water evaporation rate reaches 2.44 kgm -2 h -1 , and when 60° is incident, the water evaporation rate can also reach 1.80 kgm -2 h -1Example 2 The light-heat effect of the upper porous structure greatly decreased when facing oblique light, while Example 3 was insufficient in surface hydrophobicity after laser etching. Comparative Example 2, due to the upper surface not being treated by laser etching, although having a fast water transport effect, the light-heat efficiency greatly decreased when facing wide-angle sunlight, when 0.8 suns at 60° incidence, the water evaporation rate was 1.00 kgm -2 h -1 . Comparative Example 3, due to the lower surface not being treated by laser etching, although the upper surface had excellent wide-angle light-heat performance, the lower surface was insufficient in hydrophilicity, and the Janus structure had poor water transport effect, when 0.8 suns at 60° incidence, the water evaporation rate was 1.25 kgm -2 h -1 .
[0057] Comparative Example 4 and Comparative Example 5, two single-layer films, respectively lacked a hydrophilic layer for fast water transport and a light-heat layer for interfacial evaporation, and had poor water evaporation efficiency, when 0.8 suns were perpendicularly incident, the water evaporation rates were 0.78 and 0.35 kgm -2 h -1 .
Claims
1. A Janus-structured photothermal evaporation membrane for seawater desalination, characterized in that, The Janus structure photothermal evaporation membrane is a bilayer composite structure with asymmetric wettability, which is obtained by composite treatment of the upper superhydrophobic photothermal functional layer and the lower hydrophilic moisture transport layer.
2. The Janus structure photothermal evaporation film according to claim 1, characterized in that, The upper thin film composite solution forming the superhydrophobic photothermal functional layer includes naphthalenebiphenyl polyarylene ether sulfone ketone, polydimethylsiloxane, molybdenum disulfide nanoparticles, and N-methylpyrrolidone, with the following mass percentages of each component: Naphthyl biphenyl polyarylether sulfone ketone: polydimethylsiloxane: nano molybdenum disulfide: N-methylpyrrolidone = 1:0.2:0.01:
5.
3. The Janus structure photothermal evaporation film according to claim 2, characterized in that, The lower film composite solution that forms the hydrophilic moisture transport layer includes quaternary ammonium-based heteronaphthyl biphenyl polyarylene sulfone ketone N-methylpyrrolidone, and the mass percentages of each component are as follows: Quaternary ammonium-based naphthalene biphenyl polyarylether sulfone ketone: N-methylpyrrolidone = 1:3~10.
4. A method for preparing a Janus-structured photothermal evaporation membrane for seawater desalination as described in any one of claims 1-3, characterized in that, The steps are as follows: Step 1: Dissolve polyarylene ether sulfone ketone in N-methylpyrrolidone, then add polydimethylsiloxane, stir and mix, then add nano molybdenum disulfide dispersion, stir and mix to obtain the upper film composite solution; Step 2: After the upper thin film composite solution in Step 1 is formed into a film by the scraping method, it is immersed in deionized water for 48 hours to carry out non-solvent-induced phase separation, and then dried to obtain the surface of the upper superhydrophobic photothermal functional layer. Step 3: The upper surface of the superhydrophobic photothermal functional layer in Step 2 is designed with a micro-nano structure using nanosecond laser etching technology to obtain a superhydrophobic film with photothermal evaporation performance. Step 4: Dissolve the quaternized naphthalene-biphenyl polyarylether sulfone ketone in N-methylpyrrolidone to obtain the lower film composite solution; Step 5: The lower thin film composite solution from Step 4 is uniformly coated onto the lower surface of the superhydrophobic photothermal functional layer in Step 2 using a scraping method. After being immersed in ethyl acetate for 24 hours, non-solvent-induced phase separation is performed, and then the film is dried to obtain a bilayer composite film. Step 6: The lower surface of the double-layer composite film in Step 5 is designed with a micro-nano structure using nanosecond laser etching technology to obtain a hydrophilic surface with rapid water channels.
5. The preparation method according to claim 4, characterized in that, The parameters for the micro / nano structure design in step 3 are as follows: Laser frequency: 30KHz; current: 1A; scanning speed: 1000mm / s; laser scanning spacing: 0.02mm; scanning trajectory: cylindrical.
6. The preparation method according to claim 4, characterized in that, The parameters for micro / nano structure design in step 6 are as follows: Laser frequency: 30KHz; current: 1A; scanning speed: 1000mm / s; laser scanning spacing: 0.02mm; scanning trajectory: grid.
Citation Information
Cited By
Preparation method and application of coupled micro-nanofiber composite membrane distiller
CN121571010A